Finite element analysis of adhesively bonded composite joints subjected to impact loadings. (January 2015) - Hazimeh, R.; Challita, G.; Khalil, K.; Othman, R.
Abstract: The main concern of this paper is to explore the geometrical and material effects on composite double lap joints (DLJ) subjected to dynamic in-plane loadings. Thus, three-dimensional finite element analyses were carried out at quasi-static and impact velocities. The DLJ alone was used for quasi-static case while an output bar was added for impact case. Elastic behavior was assumed for both adhesive and adherends. Average shear stress and stress homogeneity were extracted and compared. It was observed that the adhesive shear stiffness increases the average shear stress. Moreover, it makes the stress heterogeneity more important. On the other hand, higher values of the substrates longitudinal stiffness make the average shear stress higher; whereas, the stress homogeneity in the joint is better achieved for lower substrates' shear stiffness.